Pediatric robotic assisted laparoscopic nephropexy: case study - Bansal, Danesh (Springer International Publishing, 2013)
We describe pediatric robotic assisted laparoscopic left nephropexy in a 12-year-old female for symptomatic nephroptosis after partial nephroureterectomy.